Verbal Reasoning Impairment in Parkinson’s Disease - Antonina Luca; Giulia Donzuso; Concetta D’Agate; Claudio Terravecchia; Calogero Cicero Edoardo; Giovanni Mostile; Giorgia Sciacca; Alessandra Nicoletti; Mario Zappia (Behavioural Neurology, 2022)
Background. The aim of this study was to assess verbal reasoning (VR) functioning in patients with Parkinson’s disease (PD) and healthy controls (HCs). Methods. The non-demented PD patients and HCs matched by age and global cognition were enrolled in this study. VR was assessed with the verbal reasoning test (VRT), total score, and subsets. Results. Eighty-seven PD patients (51 men; mean age 63.8±7.9 years) and 87 HCs (46 men; mean age 63.7±8.0 years) were enrolled. At univariate analysis, PD patients presented a significantly lower score in the VRT subset classification (12.3±2.1) than HCs (12.9±1.7) with an odds ratio (OR) of 0.8 (95% confidence interval [CI] 0.70–0.98; p=0.003). The strength of association was also confirmed at multivariate analysis (OR = 0.8, 95% CI 0.70–0.98; p=0.003). Moreover, in PD patients, a statistically significant positive correlation was found between VRT-classification and MoCA scores (r=0.330; p=0.002). Conclusions. PD patients presented lower VR performance than HCs.